DIAGNOSIS KESULITAN BELAJAR FISIKA SISWA PADA MATERI MOMENTUM DAN IMPULS DI SMAN SE-KECAMATAN LIMAPULUH PEKANBARU - Riyanti, Fitri Eva; Islami, Nur; Ma?aruf, Zuhdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the learning difficulties of class X students of SMAN in Limapuluh Pekanbaru. In this study, the population was all students of class X IPA of SMAN in Limapuluh Pekanbaru. The sample was taken by simple random sampling so that a sample of 72 students was obtained. The instrument of this study is in the form of diagnostic test (multiple choice four-tier) which are arranged based on the syllabus and the main concepts on material momentum and impulses. Data is collected by giving a diagnostic test to the sample. Data analysis in this study uses descriptive analysis with percentage techniques, which provide an overview of student learning difficulties. The results of this study provide information that the percentage of the average learning difficulties of senior high school students in Limapuluh Pekanbaru material momentum and the impulse of the concept of understanding the concept of 13.80% (low), the category of understanding the concept of partially 37.07% (moderate), category of misconception 44.97% (moderate) and the category does not understand the concept of 4.17% (low).Key Words: Learning Difficulties, Diagnostic Tests, Momentum And Impulses